Mexico : economic growth exports and industrial performance after NAFTA - Moreno-Bird, Juan Carlos (UN Mexico CityMX, 2005)
Looks at Mexico's industrial policy and economic performance, focusing on an analysis of the structural changes associated with NAFTA that have occurred in the country's manufacturing sector.